The Effect of Resistance Training-Based Exercise on Shot Put Performance in Physical Education Learning - Awaluddin, Awaluddin; Jamaluddin, Jamaluddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aimed to determine the effect of resistance training on shot put performance in Physical Education lessons for students at SMP Negeri 24 Makassar. The study used a quasi-experimental design with a one-group pretest-posttest. The sample consisted of 30 students selected purposively. The primary instrument used was a shot put performance test measured in meters. The resistance training program was conducted for six weeks, three times per week, and included upper-body, lower-body, core, and power drills relevant to shot put technique. The results showed a significant improvement in students' shot put performance. The average put distance increased from 5.42 meters in the pretest to 6.38 meters in the posttest. A paired sample t-test yielded a p-value <0.001, indicating a significant difference between the pretest and posttest results. The large effect size (Cohen's d = 1.78) indicates that resistance training has a strong influence on students' shot put ability. Overall, this study concludes that resistance training is an effective training method and can be implemented in physical education (PJOK) lessons to improve students' athletic skills. This program also has the potential to increase student motivation through varied and structured movement activities. These findings can serve as a reference for PJOK teachers in developing more innovative athletics learning strategies based on sports science.